Analysis of the Influence of Maqashid Syariah, Marketing Strategies, and Green Products on the Halal Lifestyle of Indonesian Alwahida Antidote Herbal Consumers in Medan City - Rizky Afifah Balqis; Anriza Witi Nasution (PT ARFA DIGITAL TECHNOLOGY, 2025)
This study analyzes the influence of Maqashid Syariah, marketing strategies, and green products on the halal lifestyle of HPAI consumers in Medan City. This study aims to determine how much influence Maqashid Syariah, marketing strategy, and green product on halal lifestyle for HPAI consumers in Medan City. The data collection technique is carried out by using questionnaires and disseminated through google forms to Herba Penawar Al-Wahida Indonesia consumers in Medan City. The population of this study is the community in Medan City with 21 districts. The sample in this study was as many as 100 respondents selected using the slovin formula. The sampling technique is carried out by random sampling. The data processing technique in this study uses the help of a tool, namely version Statistical Program for Social Science version 26. The analysis used is hypothesis analysis with partial test approaches, simultaneous tests, and determination tests. The results of this study show that Maqashid Syariah is partially influential and significant on halal lifestyle, marketing strategies are partially influential and insignificant on halal lifestyle, and green products are partially influential and significant on halal lifestyle. Maqashid Syariah variables, marketing strategies, and green products have a significant effect together (simultaneously) on halal lifestyle and influence 66.9% and the remaining 30.1% are influenced by other variables.